MicroRNA in Diabetic Nephropathy: Renin Angiotensin, AGE/RAGE, and Oxidative Stress Pathway - Shinji Hagiwara; Aaron McClelland; Phillip Kantharidis (Journal of Diabetes Research)
MicroRNAs (miRNA) are a novel class of small, noncoding RNA molecules that have gained the attention of many researchers in recent years due to their ability to posttranscriptionally regulate the expression of families of genes simultaneously. Their role in normal physiology and pathobiology is intriguing and their regulation in normal and disease states is fascinating. That the cells can return to a state of homeostasis when these small molecules are perturbed is truly remarkable given the multiple cellular targets of each miRNA and that many mRNAs are targeted by multiple miRNAs. Several reviews have covered aspects of miRNA function in biology and disease. Here, we review the role of miRNA in regulating the renin-angiotensin system, AGE/RAGE signalling, and under conditions of oxidative stress in the context of diabetic nephropathy.